1994
DOI: 10.1182/blood.v83.5.1193.1193
|View full text |Cite
|
Sign up to set email alerts
|

Intensive therapy with cyclophosphamide, carmustine, etoposide +/- cisplatin, and autologous bone marrow transplantation for Hodgkin's disease in first relapse after combination chemotherapy [see comments]

Abstract: The optimal timing in which to use intensive chemotherapy and autologous bone marrow transplantation (BMT) in Hodgkin's disease (HD) is uncertain. In 1985, we initiated a program in which this modality was used as the initial salvage therapy in patients relapsing after combination chemotherapy. Fifty-eight patients with HD in first relapse after primary chemotherapy received conditioning with high-dose cyclophosphamide, carmustine, etoposide (VP16–213) +/- cisplatin (CBV +/- P) followed by autologous BMT. All … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
27
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 202 publications
(31 citation statements)
references
References 38 publications
3
27
1
Order By: Relevance
“…induction failure) had the worst outcomes when compared with those who relapsed but the HDT regimen and ASCT were associated with 45% EFS (Moskowitz et al , 2004). For all refractory and relapsed HL, chemosensitivity to the pretransplant regimen was always a major prognostic factor for outcome after HDT (Chopra et al , 1993; Reece et al , 1994).…”
Section: Resultsmentioning
confidence: 99%
“…induction failure) had the worst outcomes when compared with those who relapsed but the HDT regimen and ASCT were associated with 45% EFS (Moskowitz et al , 2004). For all refractory and relapsed HL, chemosensitivity to the pretransplant regimen was always a major prognostic factor for outcome after HDT (Chopra et al , 1993; Reece et al , 1994).…”
Section: Resultsmentioning
confidence: 99%
“…While ASCT offers durable remission to about 50% of patients, others fare poorly even with this intensive approach. B symptoms and extranodal (EN) involvement at relapse have been identified as poor prognostic factors after ASCT, as have bulky or chemoresistant disease (Chopra et al , 1993; Reece et al , 1994; Nademanee et al , 1995; Brice et al , 1997; Horning et al , 1997; Ferme et al , 2002; Majhail et al , 2006). The impact of induction failure or early relapse (<12 months remission duration) on outcomes after ASCT is less clear, with progression‐free survival (PFS) estimates ranging widely, from 20% to 50%, in this group (Chopra et al , 1993; Nademanee et al , 1995; Brice et al , 1997; Horning et al , 1997; Sweetenham et al , 1999; Ferme et al , 2002; Majhail et al , 2006).…”
mentioning
confidence: 99%
“…The use of high-dose therapy and autologous haemopoietic stem cell transplantation has a clearly established role in the treatment of Hodgkin's disease and non-Hodgkin's lymphoma (NHL) (Reece et al, 1994;Philip et al, 1995;Freedman et al, 1996). In contrast, the place of allogeneic transplantation in lymphoma is controversial as reported studies both from single centres and from registries have shown a high transplant-related mortality (TRM).…”
mentioning
confidence: 99%